Rise and Fall of Nifty 50 Under the Influence of Market Indicators: An Analysis (International Journal of Food and Nutritional Sciences, 2023)
The purpose of this research study is to shed light on the connection between market movements and important economic and financial variables by analysing the Nifty 50 index's variations in response to several market indicators. Market performance and investor sentiment are closely tracked by the Nifty 50, a benchmark index that represents the top 50 businesses listed on the National Stock Exchange (NSE) of India. This study examines the relationship between the Nifty 50 index and market indicators like interest rates, inflation rates, FIIs, and macroeconomic variables. It does this through a thorough examination of historical data, statistical methods, and econometric models. Through an analysis of these connections, the study finds important correlations and patterns that impact the index's efficiency. This study sheds light on the factors that influence the index's volatility by showing how various market indicators impact investor actions and market tendencies. If policymakers, investors, and financial experts in India are trying to make sense of stock market patterns, this research will help them out. It also adds to our knowledge of market dynamics